Formation And Characterization Of Ketoprofen-L-Arginine Co-Amorph Using Neat Grinding Method And Its Effect On Ketoprofen Dissolution Rate - Wahyu Alfath Firdaus; Erizal Zaini; Salman Umar (Jurusan Farmasi Fakultas Kedokteran Universitas Lampung, 2026)
Ketoprofen is a non-steroidal anti-inflammatory drug (NSAID) that exhibits anti-inflammatory, analgesic, and antipyretic properties. Ketoprofen belongs to Biopharmaceutics Classification System (BCS) class II, characterized by high permeability and low solubility. This condition limits the drug absorption process and consequently results in a delayed therapeutic effect. Therefore, efforts are required to improve the solubility and dissolution rate of ketoprofen. This study aimed to enhance the dissolution rate of ketoprofen through the formation of ketoprofen–l-arginine co-amorphous systems at molar ratios of 1:1, 1:2, and 1:3. The co-amorphous systems were prepared using the neat grinding method and characterized by Powder X-Ray Diffractometry (PXRD), Differential Scanning Calorimetry (DSC), Fourier Transform Infrared (FTIR) spectroscopy, polarized light microscopy analysis, solubility testing, and dissolution rate profiling. The results indicated the successful formation of ketoprofen–l-arginine co-amorphous systems. DSC thermogram analysis showed endothermic peaks in the range of 70–240°C, while XRD spectra revealed the absence of new crystalline habit formation. Solubility testing demonstrated an increase of 3.38-, 3.21-, and 2.95-fold for the respective formulations. All ketoprofen–l-arginine co-amorphous samples were able to significantly enhance the dissolution rate of ketoprofen.